The Notion of Effectiveness in the Law of the European Union - Stępkowski, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The work submitted herein aims to address the question of effectiveness of EU law. Effectiveness of that law is subject to an ongoing controversy, as there is no agreement in legal literature either on the legal status of effectiveness or its use by the Court of Justice of the European Union. The author undertakes to outline the grounding of effectiveness in EU law in relation to both written law and jurisprudence of the Court. The work assumes the use of the descriptive approach in the legal doctrine, specifically the explanatory non-normative legal doctrine by A.R. Mackor. In this manner, this paper elects to present descriptive statements with extensive use of the Court’s case law as a feature to establish the content of applicable law. This work takes account of the law and jurisprudence as they were on 11th of October 2015.
Keywords: prawo Unii Europejskiej; system prawa Unii Europejskiej; efektowność; effet utile; skuteczność